Diakonia: In Conversation with John N. Collins - Breed, Gert (Ecclesiology, 2017)
The work of John N. Collins on the διάκον- word group makes an important contribution to understanding church ministry. Although it receives much attention and support, there is some criticism of Collins’s exegesis. If his conclusions are accepted by churches, there will be an impact on their ministry. It is therefore important that his underlying assumptions be thoroughly tested. This article analyzes Mark 10:45 in the context of that Gospel and particularly in the context of Mark 8–10. Collins’s supposition that διακονία is never done out of love or compassion for other people is found wanting. Rather, Mark describes Jesus’s διακονία as done out of compassion and love for others, and as an envoy of God.